J HEALTH PROMOT BEHAV 2017
DOI: 10.26911/thejhpb.2017.02.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personal Factors, Family Support, Pocket Money, and Peer Group, on Smoking Behavior in Adolescents in Surakarta, Central Java

Abstract: Background: According to WHO and Global Youth Tobacco Survey, Indonesia is the third largest country with current smokers in the world, including young smokers. It is widely known that smoking is hazardous to health and detrimental to economy. Surakarta is one of the major cities in Central Java where the prevalence of current smokers has been increasing among adolescents. This study aimed to determine the effect of personal factors, family support, pocket money, and peer group, on smoking behavior in adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…In Vietnam, researchers identified that exposure to tobacco advertising was associated with an increased risk of smoking among school children (13–15 years) 58 . This association was also observed in several Indonesian studies, where exposure to tobacco advertising was associated with current smoking among school students 59 , 60 and youth (11–24 years) 61 . In another Indonesian study, researchers demonstrated that a higher level of exposure to tobacco advertising was associated with increased smoking among adolescent smokers 62 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In Vietnam, researchers identified that exposure to tobacco advertising was associated with an increased risk of smoking among school children (13–15 years) 58 . This association was also observed in several Indonesian studies, where exposure to tobacco advertising was associated with current smoking among school students 59 , 60 and youth (11–24 years) 61 . In another Indonesian study, researchers demonstrated that a higher level of exposure to tobacco advertising was associated with increased smoking among adolescent smokers 62 .…”
Section: Resultssupporting
confidence: 78%
“…This study reviewed evidence related to how TAPS may influence the smoking attitudes and behaviors of youth in ASEAN countries. Studies clearly indicated that youth in the region were exposed to tobacco advertising [46][47][48][49][50][51][52][53][54][55][56][57] , and that exposure was associated with increased risk of smoking susceptibility or uptake [58][59][60][61] , as well as increased cigarette consumption among current smokers 62 . While quantitative studies suggested that school children in ASEAN countries were susceptible to tobacco advertising 68,69 , qualitative and mixed-method studies demonstrated that tobacco advertising might influence youth to form positive attitudes towards smoking and tobacco brandsparticularly around gender norms and smoking [70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
“…In connection, a counseling strategy was discussed as part of financial education and a source of learning [20]. Some may incur with illegal vices due to uncontrolled pocket money and lack of perceived behavior and counseling [21].…”
Section: Related Review Of Literaturementioning
confidence: 99%
“…Social media can function as an effective channel for adolescents to know things easily. Exposure to cigarette advertisements was also intended to give adolescents the intention to smoke indirectly increasing their idea that smoking was something that causes adolescents to have a tendency to smoke (Pandayu et al, 2017).…”
Section: The Effect Of Media Exposure Onmentioning
confidence: 99%
“…In adolescence, peer sensitivity would increase compared to other periods of life (Bruine et al, 2019). The need to be accepted among peers made them willing to do anything including smoking (Pandayu et al, 2017). Research done by Moor et al (2019) showed that adolescents chose friends based on similar behavior during the formation of friendships.…”
Section: The Effect Of Peer On Smoking Behavior Among Adolescentsmentioning
confidence: 99%